A survey on the use patterns and information needs of the Arsenio H. Lacson Public Library users with implications on collection development - Pascual, Emar G.; Faderon, Rosalie B. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1998)
This study was conducted to: 1) find out what are the purposes of the users in using the library; 2) determine what are their methods of locating information; 3) find out what sources of information are frequently used by them; 4) determine the subject areas in which the users need more information; 5) determine the library/information services that are provided to the users; 6) determine if the users are satisfied with the present collection; and 7) to come up with suggestions on how the library can effectively meet the needs of the users.
The major findings of the study are: 1) among the 180 respondents, 116 (64.4) are students; 2) most of the library users visit the library daily; 3) the major purposes of the patrons for going to the library are: "read newspapers", "read magazines", and "to borrow books"; 4) most of them locate information by going directly to the shelves; 5) the library materials that are frequently used are the popular magazines and the reference books; 6) majority of the respondents seek information in the subject area of generalities; 7) one hundred forty-eight (82.2) of the users perceive that the present library collection is good or adequate in meeting their information needs; and 8) the library services that are frequently used are the reference and circulation services.
Recommendations of the study are: 1) the City Government of Manila should provide financial support to the public library in order for it to supplement the information needs of its users and for its collection development; 2) the library collection should be expanded to cater to the needs of majority of its users; and 3) the librarians should come up with the profile of users in order that information resources needed by them may be supplied by the library. In that way, the number of users requesting the other categories may be increased. Thus, the library will be able to cater to the different sectors in the community.
Vita.
Computer print out.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Library use studies -- Philippines -- Manila; Public libraries -- Philippines -- Manila; Arsenio H. Lacson Public Library